Coupling mechanisms of plasmon resonance and Bi3+ emission in YAG: Bi, Ce, Yb epitaxial films at low temperatures - Markiyan Kushlyk; Yaroslav Shpotyuk; Volodymyr Tsiumra; Yaroslav Zhydachevskyy; Lev-Ivan Bulyk; Volodymyr Haiduchok; Ihor Syvorotka; Dmytro Sugak; Matej Baláž; Andrzej Suchocki (Scientific Reports)
Abstract This paper is devoted to the investigation of the plasmonic effect of metal nanoparticles (NPs) formed on the surface of the YAG: Bi, Ce, Yb phosphors in a temperature range between 4 and 300 K. Combination of a thin conversion layer with silver plasmonic nanostructures leads to increase of sensitizer absorption and emission efficiency. Enhancement of Bi3+ luminescence in YAG epitaxial films with Ag NPs was observed upon cooling the samples below 200 K. High enhancement factors were associated with closely matching the maximum of plasmon extinction and Bi3+ emission bands. The maximum value of enhancement factor near 170% at 4 K was obtained. It is shown that temperature decrease causes an increase in the EM field intensity around the NPs, the probability of spontaneous recombination, the penetration depth of the localized surface plasmon resonances (LSPR) into the substrate, and the adjustment of the position of the LSPR. Simultaneous action of all these factors leads to Bi3+ emission intensity enhancement. Comparative analysis of the Finite-Difference Time-Domain (FDTD) simulation data vs. experimental results of the temperature behavior of plasmon absorption spectra, luminescence spectra of Bi3+ ions, and their decay kinetics confirms the correctness of the proposed mechanisms.